2017
DOI: 10.1002/lno.10527
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of a tide‐dominated reef platform subject to extreme diel temperature and oxygen variations

Abstract: Benthic dissolved oxygen fluxes were measured on the reef flat of Tallon Island, an intertidal reef platform in the Kimberley region of northwestern Australia, for periods of 2 weeks in the wet and dry seasons. This reef flat is strongly tidally forced by semidiurnal tides (spring range > 8 m) and experiences highly asymmetric water level variability, with ebb durations lasting ∼10 h; this results in diel variations in water temperature and dissolved oxygen (DO) concentration (up to ∼11°C and 440 μM, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 85 publications
1
48
0
Order By: Relevance
“…Community NEM rates of various seafloor habitats worldwide on (A) daily and (B) annual timescales. Daily NEM (a) mean ± SD (large open symbols) and number of observations ( n ) for datasets that compute the daily NEM from continuous diel measurements over 24 h (Maerl beds: Attard et al [], Martin et al [], and Martin et al []; bare sediments: Attard et al [], Attard et al [], Berg et al [], Chipman et al [], Hume et al [], Rheuban et al [], and Walpersdorf et al []; macroalgae: Gruber et al [] and this study; Seagrass: Ganguly et al [], Gruber et al [], Hume et al [], Lee et al [], Long et al [], Moriarty et al [], Olivé et al [], Pollard and Moriarty [], and Rheuban et al []). Annual data (B) are from studies that consider daily and seasonal NEM when computing the annual estimate (Maerl beds: Attard et al [] and Martin et al []; bare sediments: Attard et al [], Chipman et al [], and Rheuban et al []; Seagrass: Rheuban et al []; Macroalgae: this study).…”
Section: Discussionmentioning
confidence: 99%
“…Community NEM rates of various seafloor habitats worldwide on (A) daily and (B) annual timescales. Daily NEM (a) mean ± SD (large open symbols) and number of observations ( n ) for datasets that compute the daily NEM from continuous diel measurements over 24 h (Maerl beds: Attard et al [], Martin et al [], and Martin et al []; bare sediments: Attard et al [], Attard et al [], Berg et al [], Chipman et al [], Hume et al [], Rheuban et al [], and Walpersdorf et al []; macroalgae: Gruber et al [] and this study; Seagrass: Ganguly et al [], Gruber et al [], Hume et al [], Lee et al [], Long et al [], Moriarty et al [], Olivé et al [], Pollard and Moriarty [], and Rheuban et al []). Annual data (B) are from studies that consider daily and seasonal NEM when computing the annual estimate (Maerl beds: Attard et al [] and Martin et al []; bare sediments: Attard et al [], Chipman et al [], and Rheuban et al []; Seagrass: Rheuban et al []; Macroalgae: this study).…”
Section: Discussionmentioning
confidence: 99%
“…a). Previous studies have addressed the hydrodynamics (Lowe et al ), thermodynamics (Lowe et al ), and community productivity (Gruber et al ) of Tallon reef.…”
Section: Methodsmentioning
confidence: 99%
“…Corals on the reef flat of the Kimberley region have to cope with extended aerial exposure during spring low tides (up to several hours, Figure 2) and periods of stagnant water alternating with strong tidal currents (>10 knots). These physical conditions create extreme fluctuations in environmental parameters, such as temperature (e.g., the well-studied Shell Island where temperature can fluctuate by up to 7 • C daily, Dandan et al, 2015;Schoepf et al, 2015), pH (e.g., Tallon Island where pH can fluctuate from 7.6 to 8.8 units over a spring low tide, Pedersen et al, 2016), dissolved oxygen (Pedersen et al, 2016;Gruber et al, 2017), unusually turbid waters, and monthly SST exceeding 30 • C for several months a year. Despite these extreme conditions, highly diverse coral reefs exist throughout the Kimberley of up to 225 species (Rosser and Veron, 2011;Richards et al, 2015), which are comparable to inshore reefs in the central GBR ∼2 decades ago (Richards et al, 2015).…”
Section: Macrotidal Coral Reef Environmentsmentioning
confidence: 99%
“…Reef flat communities of the Kimberley appear to have adapted their physiology to maintain metabolic balance of photosynthesis-to-respiration (P:R) despite the extreme physicochemical conditions of the reef-flat (Gruber et al, 2017). Furthermore, a seasonal calcification study revealed high resilience of coral calcification to both intertidal and subtidal temperature conditions as branching and massive corals calcified at rates that were comparable to those of similar species at a more typical coral reef 1,200 km to the southwest (Ningaloo Reef; Dandan et al, 2015).…”
Section: Macrotidal Coral Reef Environmentsmentioning
confidence: 99%
See 1 more Smart Citation